Đơn giản biểu thức A = √(9+4√5)+√(9-4√5)

Đơn giản biểu thức A = √(9+4√5)+√(9-4√5)

Share

1 Answer

  1. Đáp án:

    Giải thích các bước giải:

    \[\begin{array}{l}A{\rm{ }} = {\rm{ }}\surd \left( {9 + 4\surd 5} \right) + \surd \left( {9 – 4\surd 5} \right)\\A = \sqrt {\left( {9 + 4\sqrt 5 } \right)} + \sqrt {\left( {9 – 4\sqrt 5 } \right)} \\ = \sqrt {{2^2} + 2.2\sqrt 5 + {{\left( {\sqrt 5 } \right)}^2}} + \sqrt {{2^2} – 2.2\sqrt 5 + {{\left( {\sqrt 5 } \right)}^2}} \\ = \sqrt {{{\left( {2 + \sqrt 5 } \right)}^2}} + \sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} \\ = \left| {2 + \sqrt 5 } \right| + \left| {2 – \sqrt 5 } \right|\\ = 2 + \sqrt 5 – \left( {2 – \sqrt 5 } \right)\,\,\,\,\,\,\,\left( {vi\,\,\,\,{2^2} < {{\left( {\sqrt 5 } \right)}^2} \Rightarrow 2 < \sqrt 5 } \right)\\ = 2 + \sqrt 5 - 2 + \sqrt 5 \\ = 2\sqrt 5 \end{array}\]

    • 0
Leave an answer

Leave an answer

Browse